Negative electrode active material, negative electrode pole piece, sodium ion battery and electric device

By using hard carbon and converted sodium storage materials with suitable true density in the negative electrode active materials of sodium ion batteries, the problem of thermal runaway in the sodium ion battery is solved and higher safety and capacity are achieved.

CN119890243APending Publication Date: 2025-04-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311378852.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

Smart Images

  • Figure CN119890243A_ABST
    Figure CN119890243A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a negative electrode active material, a negative electrode plate, a sodium ion battery and an electric device. The negative electrode active material comprises hard carbon, and the true density rho of the hard carbon is greater than or equal to 1.3 g / cm < 3 > and less than or equal to 2.0 g / cm < 3 >; and a conversion type sodium storage material, wherein the conversion type sodium storage material can form a compound with sodium. When the negative electrode active material is applied to the sodium ion battery, the thermal runaway risk of the sodium ion battery can be effectively reduced, and the safety performance of the sodium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a negative electrode active material, a negative electrode plate, a sodium ion battery and an electrical device. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have the advantages of low cost and abundant sodium resources. They can be used as a substitute for lithium-ion batteries and show great application potential in markets such as large-scale energy storage and passenger cars. Hard carbon has a low operating voltage and good cycle stability and is considered to be the most promising negative electrode material for sodium-ion batteries.

[0003] However, sodium-ion batteries face problems such as short circuit and thermal runaway during actual use. When short circuit and thermal runaway problems occur, hard carbon will form a large amount of metallic sodium during the battery cycle due to its sodium storage mechanism. When the battery has thermal runaway, the thermal runaway will be rapidly aggravated, and in severe cases, the sodium-ion battery will catch fire and explode. Therefore, how to improve the thermal runaway problem of sodium-ion batteries has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application is made in view of the above-mentioned technical problems, and its purpose is to provide a negative electrode active material, a negative electrode plate, a sodium ion battery and an electrical device, wherein the negative electrode active material can effectively reduce the thermal runaway risk of the sodium ion battery.

[0005] In a first aspect, a negative electrode active material is provided, comprising: hard carbon, wherein the true density ρ of the hard carbon satisfies: 1.3 g / cm 3 ≤ρ≤2.0g / cm 3 ; A conversion-type sodium storage material, which can form a compound with sodium.

[0006] In the embodiment of the present application, the negative electrode active material includes a true density of 1.3 g / cm 3 -2.0g / cm 3 Hard carbon conversion type sodium storage materials within the range, hard carbon with true density within the above range can provide higher capacity for sodium ion batteries, and conversion type sodium storage materials allow sodium ions to be embedded therein, forming compounds with them to store sodium, thereby reducing the generation of metallic sodium during battery cycling, which helps to reduce the risk of thermal runaway of sodium ion batteries. In addition, sodium compounds usually have a higher melting point, and in the event of thermal runaway, thermal runaway will not spread rapidly, which helps to improve the safety performance of sodium ion batteries.

[0007] In one embodiment, the mass content m1 of the hard carbon in the negative electrode active material satisfies: 80%≤m1≤99%; alternatively, 85%≤m1≤98%.

[0008] In one embodiment, the mass content m2 of the conversion-type sodium storage material in the negative electrode active material satisfies: 1%≤m2≤20%; optionally, 2%≤m2≤15%.

[0009] In the embodiments of the present application, by regulating the mass content of hard carbon and conversion-type sodium storage material in the negative electrode active material, the capacity and sodium storage mechanism of the negative electrode active material can be effectively regulated, and the formation of metallic sodium can be reduced. As a result, when the negative electrode active material is used in a sodium ion battery, the sodium ion battery can have both high capacity and good safety.

[0010] In one embodiment, the conversion-type sodium storage material includes at least one of an alloy sodium storage material, a metal oxide sodium storage material, a metal sulfide sodium storage material, a metal selenide sodium storage material, and a metal phosphide sodium storage material.

[0011] In one embodiment, the alloy sodium storage material includes at least one of Sn, Ge, Pb, P, Sb, Bi, Si and alloys thereof.

[0012] In one embodiment, the metal oxide sodium storage material includes at least one of Sn oxide, Ge oxide, Pb oxide, P oxide, Sb oxide, Bi oxide, and Si oxide.

[0013] In one embodiment, the metal sulfide sodium storage material includes at least one of: Sn sulfide, Ge sulfide, Pb sulfide, P sulfide, Sb sulfide, Bi sulfide, and Si sulfide.

[0014] In one possible implementation, the metal selenide sodium storage material includes at least one of: Sn selenide, Ge selenide, Pb selenide, P selenide, Sb selenide, Bi selenide, and Si selenide.

[0015] In one embodiment, the metal phosphide sodium storage material includes at least one of: Sn phosphide, Ge phosphide, Pb phosphide, Sb phosphide, Bi phosphide, and Si phosphide.

[0016] In one embodiment, the compound formed by the conversion-type sodium storage material and sodium includes at least one of a sodium alloy, a sodium oxide, a sodium sulfide, a sodium selenide, and a sodium phosphide.

[0017] In one embodiment, the average volume particle size distribution Dv50 of the conversion-type sodium storage material satisfies: 3.5 μm≤Dv50≤6.5 μm; optionally, 4 μm≤Dv50≤6 μm.

[0018] In one embodiment, the specific surface area BET of the conversion type sodium storage material satisfies: 3m 2 / g≤BET≤15m 2 / g; optionally, 4m 2 / g≤BET≤10m 2 / g.

[0019] In one embodiment, the negative electrode active material has a powder compaction density α of 0.85 g / cm2 at a pressure of 3 T. 3 ≤α≤1.6g / cm 3 ; Optionally, 0.88 g / cm 3 ≤α≤1.5g / cm 3 .

[0020] In one possible implementation, the gram capacity W1 of the hard carbon satisfies: 150 mAh / g≤W1≤350 mAh / g; optionally, 280≤W1≤350 mAh / g.

[0021] In one embodiment, the discharge gram capacity W2 of the conversion-type sodium storage material satisfies: 300mAh / g≤W2≤2000mAh / g; optionally, 300mAh / g≤W2≤1500mAh / g.

[0022] In a second aspect, a negative electrode plate is provided, wherein the negative electrode plate comprises the negative electrode active material in any possible implementation manner of the first aspect.

[0023] In a third aspect, a sodium ion battery is provided, wherein the sodium ion battery comprises the negative electrode plate in any embodiment of the second aspect.

[0024] In a fourth aspect, an electrical device is provided, wherein the electrical device comprises a sodium ion battery in any embodiment of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0026] Figure 1 This is a schematic diagram of a sodium ion battery cell according to an embodiment of the present application.

[0027] Figure 2 This is a schematic diagram of a sodium ion battery module according to an embodiment of the present application.

[0028] Figure 3This is a schematic diagram of a sodium ion battery according to an embodiment of the present application.

[0029] Figure 4 Another schematic diagram of a sodium ion battery according to an embodiment of the present application. DETAILED DESCRIPTION

[0030] Hereinafter, the embodiments of the negative electrode active material, negative electrode sheet, sodium ion battery and electric device of the present application are specifically disclosed with appropriate reference to the drawings in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0031] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0032] In the description of this application, it should be noted that, unless otherwise specified, "multiple" means more than two; the terms "upper", "lower", "left", "right", "inner", "outer", etc., indicating directions or positional relationships, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting this application. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0034] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0035] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0036] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their generally accepted meanings in the art.

[0037] As mentioned, "hard carbon" refers to disordered carbon materials that cannot form a regular graphite structure at high temperatures above 3000°C. Its precursors are generally polymers with multiple heteroatoms, such as sugar, cellulose, phenolic resin, etc.

[0038] As mentioned, "true density" refers to the actual mass of a solid substance per unit volume when the material is absolutely dense, that is, the density after removing the internal pores or spaces between particles.

[0039] As mentioned, "conversion-type sodium storage material" refers to a material into which sodium ions can be embedded and react chemically with it to form a compound, such as a metal, alloy, metal oxide, metal sulfide, metal tinide, etc.

[0040] As mentioned, "alloy-based sodium storage materials" refer to materials that can form alloys with sodium. In electrochemical reactions, sodium storage is based on alloying and dealloying with sodium. For example, Sn, Sb, Pb, Ge, P, etc.

[0041] As mentioned, "metal oxide sodium storage material" refers to a metal oxide that can allow sodium ions to be intercalated therein, react with sodium ions to form sodium oxide, and store sodium based on the conversion reaction between sodium and metal oxide. For example, NiCo2O4, Sb2O3, Co3O4, Fe3O4, Fe2O3, SnO, SnO2, etc.

[0042] As mentioned, "metal sulfide sodium storage material" refers to a metal sulfide that can allow sodium ions to be intercalated therein and form sodium sulfide with the sodium ions. It stores sodium based on the conversion reaction between sodium. For example, FeS, SnS2, CoS, Ni2S3, MoS2, ZnS, TiS2, etc.

[0043] As mentioned, the "discharge curve" refers to a graph showing the relationship between the electrode potential and the battery capacity during the discharge process of a battery when a certain material is used as an electrode active material.

[0044] Typically, a battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the charge and discharge process of the battery cell, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time to allow active ions to pass through. In some embodiments, the above-mentioned battery cell is also called a secondary battery.

[0045] During the charging process of sodium-ion batteries, sodium ions are released from the positive electrode active material, moved and embedded in the negative electrode material; while during the discharging process, sodium ions are released from the negative electrode material, moved and embedded in the positive electrode active material.

[0046] It should be understood that the "embedding" process described in this application refers to the process in which sodium ions are embedded in the positive electrode active material and the negative electrode material due to an electrochemical reaction, and the "extraction" and "de-intercalation" processes described in this application refer to the process in which sodium ions are extracted from the positive electrode active material and the negative electrode material due to an electrochemical reaction.

[0047] With the in-depth research and application of sodium-ion batteries, new requirements have been put forward for the capacity and safety performance of sodium-ion batteries. For example, in some application scenarios (such as electric vehicles and other electrical devices), once a short circuit occurs in the battery, the internal temperature of the battery will rise rapidly and then thermal runaway will occur, which is not conducive to the user of the electrical device to respond to it. In addition, for sodium-ion batteries, hard carbon is usually used as the negative electrode active material. At present, the process of sodium storage in hard carbon in sodium-ion batteries is generally considered to have three mechanisms: (1) the adsorption mechanism of sodium ions at the edge defects of the graphite-like layer and the surface open pores; (2) the embedding mechanism of sodium ions in the interlayer of the graphite-like layer and the detachment; and (3) the pore filling mechanism of sodium ions depositing in the closed pores and some open pores of hard carbon to form metallic sodium. Among them, the pore filling mechanism is considered to be the main mechanism contributing to the capacity of sodium-ion batteries, that is, the higher the capacity of the sodium-ion battery, the more metallic sodium is formed during the charge and discharge process of the battery. Based on this, in the aforementioned application scenario, once a short circuit occurs in the battery, the sodium-ion battery with hard carbon as the negative electrode active material is more prone to thermal runaway at the negative electrode because the thermal reaction temperature of hard carbon itself is lower than that of graphite and there is a large amount of metallic sodium. Once thermal runaway occurs, the heat will spread rapidly, and in severe cases, it will cause thermal runaway of the entire sodium-ion battery, seriously affecting the safety of the sodium-ion battery.

[0048] In view of this, the present application provides a negative electrode active material, a negative electrode plate, a sodium ion battery and an electrical device. In addition to hard carbon, the negative electrode active material also includes a conversion type sodium storage material, which can adjust the sodium storage mechanism of the negative electrode active material and effectively reduce the risk of thermal runaway of sodium ions.

[0049] First, an embodiment of the present application provides a negative electrode active material, including hard carbon and a conversion type sodium storage material capable of forming a compound with sodium. The true density ρ of the hard carbon satisfies: 1.3 g / cm 3 ≤ρ≤2.0g / cm 3 .

[0050] Specifically, ρ can be 1.3 g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , or its value is within the range obtained by combining any two of the above values.

[0051] Conversion-type sodium storage materials store sodium mainly through an embedding mechanism, which allows sodium ions to embed and react chemically with sodium ions to form sodium compounds. Hard carbon stores sodium mainly through a pore-filling mechanism, and metallic sodium is formed during the sodium storage process. The thermal reaction temperature of hard carbon itself is low, and the risk of thermal runaway is high; the metallic sodium generated by hard carbon during the sodium storage process has a low melting point, and will rapidly deteriorate the thermal runaway situation in the case of thermal runaway. However, the melting point of sodium compounds is high, and the temperature of sodium-ion batteries during thermal runaway usually cannot reach its melting point. Based on this, for negative electrode active materials, by introducing conversion-type sodium storage materials, the formation of metallic sodium can be effectively reduced, the risk of thermal runaway in sodium-ion batteries can be reduced, and the speed of heat spread can be slowed down in the event of thermal runaway. Thereby, it helps to improve the safety of sodium-ion batteries. Especially in the scenario where sodium-ion batteries are used in passenger cars, it can buy passengers a certain amount of escape time.

[0052] In one embodiment, the mass content m1 of the hard carbon in the negative electrode active material satisfies: 80%≤m1≤99%; alternatively, 85%≤m1≤98%.

[0053] Specifically, m1 can be 80%, 80.5%, 81%, 81.5%, 82%, 82.5%, 83%, 83.5%, 84%, 84.5%, 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, or any other value within the range obtained by combining any two of the above values.

[0054] Hard carbon has a high reversible capacity. It can be selected as the main material in the negative electrode active material. Controlling its mass content within a higher range will help improve the gram capacity of the negative electrode active material.

[0055] In one embodiment, the mass content m2 of the conversion-type sodium storage material in the negative electrode active material satisfies: 1%≤m2≤20%; optionally, 2%≤m2≤15%.

[0056] Specifically, m2 can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, or any other value within the range obtained by combining any two of the above values.

[0057] The conversion type sodium storage material also has a high capacity and good safety performance, but its cycle stability is not as good as that of hard carbon. Therefore, by controlling the mass content of the conversion type sodium storage material within a suitable range, the safety of the negative electrode active material can be improved while making the negative electrode active material have good cycle performance.

[0058] In the embodiments of the present application, by regulating the proportion of hard carbon and conversion-type sodium storage materials in the negative electrode active material, the sodium storage mechanism of the negative electrode active material can be regulated, the contribution of the embedding-type sodium storage material based on the embedding mechanism to the capacity of the sodium ion battery can be increased, the generation of metallic sodium can be reduced, and the possibility of thermal runaway of the sodium ion battery can be reduced.

[0059] In one embodiment, the conversion-type sodium storage material includes at least one of an alloy sodium storage material, a metal oxide sodium storage material, a metal sulfide sodium storage material, a metal selenide sodium storage material, and a metal phosphide sodium storage material.

[0060] In one embodiment, the alloy sodium storage material includes at least one of Sn, Ge, Pb, P, Sb, Bi, Si and alloys thereof.

[0061] Alloy sodium storage materials usually have a higher capacity, but when used alone as active materials to store sodium, their large volume expansion rate is not conducive to the reversible capacity and cycle stability of sodium-ion batteries. Sodium can react with alloy sodium storage materials to form alloy compounds, namely sodium-metal alloys. The melting point of sodium-metal alloys is much higher than that of metallic sodium. Therefore, by introducing alloy sodium storage materials into negative electrode active materials, the risk of thermal runaway in sodium-ion batteries can be reduced, and in the event of thermal runaway in sodium-ion batteries, the diffusion rate of heat spread can be reduced, effectively improving the safety performance of sodium-ion batteries.

[0062] It should be understood that if a metal exists in multiple different crystal forms, the above chemical formula may represent the metal including its different crystal forms.

[0063] In one embodiment, the metal oxide sodium storage material includes at least one of Sn oxide, Ge oxide, Pb oxide, P oxide, Sb oxide, Bi oxide, and Si oxide.

[0064] In one embodiment, the metal sulfide sodium storage material includes at least one of Sn sulfide, Ge sulfide, Pb sulfide, P sulfide, Sb sulfide, Bi sulfide, and Si sulfide.

[0065] In one embodiment, the metal selenide sodium storage material includes at least one of: Sn selenide, Ge selenide, Pb selenide, P selenide, Sb selenide, Bi selenide, and Si selenide.

[0066] In one embodiment, the metal phosphide sodium storage material includes at least one of Sn phosphide, Ge phosphide, Pb phosphide, Sb phosphide, Bi phosphide, and Si phosphide.

[0067] The principle of sodium storage in metal oxides, sulfides, selenides, and phosphides is based on the conversion reaction between sodium and multiple electrons. They also have high capacity, but their cycle performance is unstable when used alone as negative electrode active materials. Sodium can react with metal oxides, metal sulfides, metal selenides, and metal phosphides to form compounds with sodium, such as sodium oxides, sodium sulfides, sodium selenides, and sodium phosphides. Sodium compounds have a melting point much higher than that of metallic sodium. Therefore, by introducing metal oxides, metal sulfides, metal selenides, and metal phosphides into negative electrode active materials with hard carbon as the main material, the risk of thermal runaway in sodium-ion batteries can be reduced, and in the case of thermal runaway in sodium-ion batteries, the diffusion rate of heat spread can be reduced, effectively improving the safety performance of sodium-ion batteries.

[0068] In one embodiment, the compound formed by the conversion-type sodium storage material and sodium includes at least one of a sodium alloy, a sodium oxide, a sodium sulfide, a sodium selenide, and a sodium phosphide.

[0069] In one embodiment, the average volume particle size Dv50 of the conversion type sodium storage material satisfies: 5μm≤Dv502≤30μm; optionally, 5μm≤Dv502≤25μm. Specifically, the average volume particle size Dv502 of the conversion type sodium storage material can be: 5μm, 7μm, 9μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 25μm, 26μm, 28μm, 30μm, or its value is within the range obtained by combining any two of the above values.

[0070] In the embodiments of the present application, by controlling the average volume particle size of the hard carbon within a suitable range, it helps to reduce battery polarization and help improve the cycle performance of the sodium ion battery.

[0071] In one embodiment, the average volume particle size Dv50 of the hard carbon material satisfies: 3.5μm≤Dv501≤6.5μm; optionally, 4μm≤Dv501≤6μm. Specifically, the average volume particle size Dv501 of the hard carbon can be: 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, or its value is within the range obtained by combining any two of the above values. It should be understood that the subscripts "1" and "2" in "Dv501" and "Dv502" are only used for distinction, and are set to avoid confusion between the average volume particle size of the conversion material or the hard carbon, and do not cause other limitations.

[0072] In the embodiments of the present application, by controlling the average volume particle size of the conversion-type sodium storage material in the negative electrode active material within a suitable range, it helps to embed and extract sodium ions when applied to a sodium ion battery, so that the capacity of the negative electrode active material is more fully released, thereby helping to improve the energy density of the sodium ion battery.

[0073] In one embodiment, the specific surface area BET of the conversion type sodium storage material satisfies: 3m 2 / g≤BET≤15m 2 / g; optionally, 4m 2 / g≤BET≤10m 2 / g.

[0074] Specifically, the specific surface area BET of the conversion type sodium storage material can be: 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, or its numerical range is within the range obtained by combining any two of the above numerical values.

[0075] In one embodiment, the powder compaction density α of the negative electrode active material under a pressure of 3T satisfies: 0.85 g / cm 3 ≤α≤1.6g / cm 3 ; Optionally, 0.88 g / cm3 ≤α≤1.5g / cm 3 .

[0076] Specifically, α can be 0.85 g / cm 3 , 0.88g / cm 3 , 0.9g / cm 3 , 0.92g / cm 3 、0.94g / cm 3 、0.96g / cm 3 、0.98g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , or its numerical range is within the range obtained by combining any two of the above numerical values.

[0077] In one embodiment, the gram capacity W1 of the hard carbon satisfies: 150 mAh / g≤W1≤350 mAh / g; alternatively, 280 mAh / g≤W1≤350 mAh / g.

[0078] Specifically, W1 can be 150mAh / g, 180mAh / g, 200mAh / g, 220mAh / g, 240mAh / g, 260mAh / g, 280mAh / g, 300mAh / g, 320mAh / g, 340mAh / g, 350mAh / g, or its numerical range is within the range obtained by combining any two of the above numerical values.

[0079] In one embodiment, the gram capacity W2 of the conversion-type sodium storage material satisfies: 300mAh / g≤W2≤2000mAh / g; optionally, 300mAh / g≤W2≤1500mAh / g.

[0080] Specifically, W2 can be 300mAh / g, 400mAh / g, 500mAh / g, 600mAh / g, 700mAh / g, 800mAh / g, 900mAh / g, 1000mAh / g, 1100mAh / g, 1200mAh / g, 1300mAh / g, 1400mAh / g, 1500mAh / g, 1600mAh / g, 1700mAh / g, 1800mAh / g, 1900mAh / g, 2000mAh / g, or its numerical range is within the range obtained by combining any two of the above numerical values.

[0081] Among the negative electrode active materials provided in the present application, both hard carbon and conversion-type sodium storage materials have relatively high gram capacity, and the negative electrode active material obtained by compounding the two also has relatively high gram capacity, and can be applied to high-capacity, high-energy-density sodium-ion batteries.

[0082] Next, the electrode materials, positive electrode sheets, negative electrode sheets, separators and electrolytes in sodium-ion batteries are introduced in detail.

[0083] [Negative electrode]

[0084] The negative electrode sheet generally includes a negative electrode current collector, or includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0085] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer may be disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0086] Alternatively, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0087] Optionally, the negative electrode active material may also include a negative electrode active material for sodium ion batteries known in the art. For example, the negative electrode active material may also include at least one of the following materials: natural graphite, artificial graphite, mesophase microcarbon beads (MCMB). These negative electrode active materials may be used alone or in combination of two or more materials.

[0088] Optionally, the negative electrode film layer further includes a conductive agent, and the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0089] Optionally, the negative electrode film layer also includes a binder, which may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0090] The above-mentioned negative electrode sheet can be prepared according to conventional methods in the art. For example, the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, can be dispersed in a solvent to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0091] The negative electrode plate provided in the present application includes the negative electrode active material in the aforementioned embodiment. Therefore, when applied to a sodium ion battery, the negative electrode active material on the surface of the negative electrode plate can be obtained by disassembling the sodium ion battery and performing XRD detection on it to determine the components of its negative electrode active material, and the negative electrode active material in the aforementioned embodiment can be detected. In addition, after the sodium ion battery is cycled, the negative electrode active material on the surface of the negative electrode plate after the cycle is obtained by disassembling the sodium ion battery after the cycle and performing XRD detection on it, and the compound formed by the sodium storage material and sodium can be detected. For example, at least one of sodium alloy, sodium oxide, sodium sulfide, sodium selenide, and sodium phosphide.

[0092] [Positive electrode]

[0093] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.

[0094] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer can be disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0095] Alternatively, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0096] Optionally, the positive electrode active material may include a positive electrode active material for sodium ion batteries known in the art. As described above, the positive electrode active material may include one or more of a polyanionic compound, a transition metal oxide, and a Prussian blue compound. As an example, a polyanionic compound may be a class of compounds having sodium ions, transition metal ions, and tetrahedral anion units, such as sodium iron phosphate (NaFePO4), sodium vanadium phosphate (Na3V2(PO4)3), and the like. The transition metal oxide may be a transition metal oxide having sodium ions, such as sodium copper iron manganate, sodium iron nickel manganate, and the like. The Prussian blue compound may be a class of compounds having sodium ions, transition metal ions, and cyanide ions. However, the present application is not limited to these materials, and other materials that can be used as positive electrode active materials for sodium ion batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more materials.

[0097] Optionally, the positive electrode film layer also includes a binder, which may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0098] Optionally, the positive electrode film layer further includes a conductive agent, and the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0099] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, additives, conductive agent, binder and any other components are dispersed in a solvent (such as NMP) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0100] [Electrolytes]

[0101] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0102] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0103] Optionally, the electrolyte salt includes NaPF6, NaBCl4, NaSO3CF3 and Na(CH3)C6H4SO3, etc.

[0104] Optionally, the solvent includes carbonate or ether solvents. Carbonate solvents include cyclic ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC) and chain dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), etc.; ether solvents include ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, etc.

[0105] Optionally, the electrolyte may further include electrolyte additives. For example, the electrolyte additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0106] [Isolator]

[0107] In some embodiments, the sodium ion battery further includes a separator. The present application has no particular restrictions on the type of separator, for example, the separator may be a separator membrane. The separator membrane may be any known porous structure separator membrane with good chemical stability and mechanical stability.

[0108] Optionally, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0109] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0110] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0111] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0112] [Sodium-ion battery]

[0113] The present application also provides a sodium ion battery, which includes the negative electrode plate in any of the aforementioned embodiments.

[0114] The present application has no particular restrictions on the shape of the sodium ion battery, which can be cylindrical, square or any other shape. For example, Figure 1A sodium ion battery 100 having a square structure is shown as an example.

[0115] Figure 2 2 is a battery module 200 of a sodium ion battery as an example. Figure 2 In the battery module 200, the plurality of sodium ion batteries 100 may be arranged in sequence along the length direction of the battery module 200. Of course, they may also be arranged in any other manner. Further, the plurality of sodium ion batteries 100 may be fixed by fasteners.

[0116] Optionally, in one embodiment, the battery module 200 may further include a housing having a housing space, and the plurality of sodium ion batteries 100 are accommodated in the housing space.

[0117] Optionally, in one embodiment, the battery modules 200 may also be assembled into a battery pack. The battery pack may contain one or more battery modules 200, and the specific number may be selected by those skilled in the art according to the application scenario and capacity of the battery pack.

[0118] Figure 3 and Figure 4 300 is an example of a battery pack. Figure 3 and Figure 4 The battery pack 300 may include a battery box and a plurality of battery modules 200 disposed in the battery box. The battery box includes an upper box body 301 and a lower box body 302. The upper box body 301 can cover the lower box body 302 and form a closed space for accommodating the battery modules 200. The plurality of battery modules 200 may be arranged in the battery box in any manner.

[0119] It should be understood that in other embodiments, the battery pack 300 is also referred to as a battery. The sodium ion battery 100 may first be formed into a battery module 200, and the battery pack 300 is composed of the battery module 200. The battery pack 300 may also be directly formed of the sodium ion battery 100, omitting the intermediate form of the battery module 200.

[0120] In addition, the present application also provides an electrical device, which includes at least one of the sodium ion battery 100, battery module 200, or battery pack 300 provided in the present application. The sodium ion battery 100, battery module 200, or battery pack 300 can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0121] As an electrical device, the number of sodium ion batteries 100, battery modules 200, or battery packs 300 can be selected according to its usage requirements.

[0122] As an example of an electric device, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of secondary batteries, a battery pack 300 or a battery module 200 may be used.

[0123] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a sodium ion battery 100 may be used as a power source.

[0124] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0125] [Examples and Comparative Examples]

[0126] Example 1

[0127] (1) Preparation of positive electrode sheet

[0128] The positive electrode active material NaFe 0.33 Mn 0.33 Ni 0.33 O2, conductive agent carbon black, and adhesive polyvinylidene fluoride (PVDF) are fully and evenly mixed in a proper amount of NMP in a mass ratio of 8:1:1 to form a positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying and rolling.

[0129] (2) Preparation of negative electrode sheet

[0130] The negative electrode active material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully and evenly mixed in a proper amount of NMP at a mass ratio of 8:1:1 to form a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained after drying and rolling.

[0131] The negative electrode active material includes hard carbon and conversion type sodium storage material. The conversion type sodium storage material is Sn, with an average volume particle size distribution of Dv502 = 6 μm, a gram capacity of W2 = 720 mAh / g, and a mass content of m2 = 2.5% in the negative electrode active material; the true density of hard carbon is ρ = 1.5 g / cm 3The mass content of hard carbon in the negative electrode active material is m1 = 97.5%, and the gram capacity of hard carbon is W1 = 315 mAh / g. The powder compaction density of the negative electrode active material is measured to be α = 1 g / cm 3 .

[0132] (3) Assembly of sodium ion batteries

[0133] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order so that the separator is between the positive electrode sheet and the negative electrode sheet. After the stacking process, an electrode assembly is formed. The electrode assembly is loaded into a packaging shell, and a NaPF6 electrolyte with a concentration of 1 mol / L is added. After packaging, formation, standing and other processes, a sodium ion battery is obtained.

[0134] Example 2

[0135] Compared with Example 1, in Example 2, ρ = 1.5 g / cm 3 , W1 = 350 mAh / g.

[0136] Example 3

[0137] Compared with Example 1, in Example 3, ρ = 2.0 g / cm 3 , W1=280mAh / g.

[0138] Example 4

[0139] Compared with Example 1, in Example 4, m1=80% and m2=20%.

[0140] Example 5

[0141] Compared with Example 1, in Example 5, m1=99%, m2=1%.

[0142] Example 6

[0143] Compared with Example 1, in Example 6, m1=70% and m2=30%.

[0144] Example 7

[0145] Compared with Example 1, in Example 7, the conversion-type sodium storage material is Bi, Dv502=5.8μm, and W2=550mAh / g.

[0146] Example 8

[0147] Compared with Example 1, in Example 8, the conversion-type sodium storage material is Sb, Dv502=5.4μm, and W2=490mAh / g.

[0148] Example 9

[0149] Compared with Example 1, in Example 9, the conversion-type sodium storage material is P, Dv502=6.1 μm, and W2=1500 mAh / g.

[0150] Example 10

[0151] Compared with Example 1, in Example 10, the conversion-type sodium storage material is SnO2, Dv502=6μm, and W2=700mAh / g.

[0152] Embodiment 11

[0153] Compared with Example 1, in Example 11, Dv502=15μm, W2=695mAh / g.

[0154] Example 12

[0155] Compared with Example 1, in Example 12, Dv502=25 μm, W2=680 mAh / g.

[0156] Example 13

[0157] Compared with Example 1, in Example 13, the embedded sodium storage material is Si, Dv502=6μm, and W2=300mAh / g.

[0158] Comparative Example 1

[0159] Compared with Example 1, in Comparative Example 1, only hard carbon is used as the negative electrode active material.

[0160] Comparative Example 2

[0161] Compared with Example 1, the true density of the hard carbon in Comparative Example 2 is ρ=2.3 g / cm 3 , the gram capacity of hard carbon is W1 = 70 mAh / g.

[0162] Table 1 Product parameters of the embodiments and comparative examples

[0163] In Table 1, "ρ" represents the true density of hard carbon in the negative electrode active material, "m1" represents the mass content of hard carbon in the negative electrode active material, "W1" represents the gram capacity of hard carbon, "conversion-type sodium storage material" represents the type of conversion-type sodium storage material in the negative electrode active material, "m2" represents the mass content of conversion-type sodium storage material in the negative electrode active material, "Dv502" represents the average volume particle size of the conversion-type sodium storage material, and "W2" represents the gram capacity of the conversion-type sodium storage material.

[0164] The performance test results of the sodium ion batteries of the above embodiments and comparative examples are shown in Table 2.

[0165] Table 2 Battery performance test results of different embodiments and comparative examples Battery energy density (Wh / kg) Heat spread rate (m / s) Example 1 120 >0.15 Example 2 127 >0.15 Example 3 110 >0.15 Example 4 125 >0.15 Example 5 113 >0.15 Example 6 130 >0.15 Example 7 117 >0.15 Example 8 115 >0.15 Example 9 123 >0.15 Example 10 119 >0.15 Embodiment 11 121 >0.15 Example 12 118 >0.15 Example 13 114 >0.15 Comparative Example 1 109 ≤0.15 Comparative Example 2 60 ≤0.15

[0166] In Table 2, "battery energy density" indicates the energy density of each sodium ion battery in the embodiments and comparative examples, and "heat propagation rate" indicates the heat propagation rate measured when the negative electrode sheet is taken out after disassembling the sodium ion battery and subjected to a heat propagation test.

[0167] According to the comparative analysis of the embodiments and the comparative examples, in the sodium ion batteries of the embodiments 1-13, the negative electrode active material includes a 3 -1.8g / cm 3 The heat spread rate of the sodium ion battery in the heat spread test is greater than 0.15m / s, while in Comparative Examples 1-2, there is no conversion-type sodium storage material that can react with sodium to form a sodium compound in the negative electrode active material, or the true density of the hard carbon is not within an appropriate range. In the heat spread test, the heat spread rate is less than or equal to 0.15m / s, and the energy density of the embodiments is better than that of the comparative examples. Therefore, it is shown that by matching hard carbon and conversion-type sodium storage materials with true density within an appropriate range, the formation of metallic sodium during the sodium ion battery cycle can be reduced, the risk of thermal runaway and heat spread of the sodium ion battery can be effectively reduced, and the sodium ion battery can have a higher energy density.

[0168] According to the data comparison of Examples 1-3 and Comparative Example 2, the greater the true density of the hard carbon, the lower the gram capacity. The possible mechanism is: the hard carbon structure with a larger true density is closer to graphite, and the sodium storage capacity of graphite is extremely low. The closer the structure is to graphite, the weaker the sodium storage capacity of the material, the lower the gram capacity, and the less contribution to the energy density. Therefore, by selecting hard carbon with a true density within a suitable range, the negative active material provided in the embodiment of the present application can reduce the risk of thermal runaway and heat spread of sodium ion batteries while having a higher energy density.

[0169] According to the data comparison of Examples 1, 4-6, increasing the mass content of the conversion type sodium storage material in the negative electrode active material helps to improve the energy density of the sodium ion battery. While considering the cycle stability of the sodium ion battery, by controlling the mass content of the conversion type sodium storage material within a suitable range, the energy density of the sodium ion battery can be improved while reducing the risk of thermal runaway and heat spread of the sodium ion battery.

[0170] Examples 7-10 and 13 show examples of different types of conversion-type sodium storage materials compounded with hard carbon. It can be seen that different types of conversion-type sodium storage materials can reduce the risk of thermal runaway and heat spread of sodium-ion batteries and enable sodium-ion batteries to have a higher energy density.

[0171] According to the data comparison of Examples 1 and 11-12, the gram capacity of the embedded sodium storage material with a smaller Dv50 is higher. The possible mechanism is: the larger the particle size of the material, the greater the distance that the sodium ions need to move to embed into it, and the internal sodium storage site may not be able to effectively store sodium during the actual battery cycle. Therefore, the embedded sodium storage material with a small particle size is more conducive to the embedding of sodium ions, and the actual number of sodium ions that can be stored is closer to the theoretical value, showing a higher gram capacity. Therefore, by selecting an embedded sodium storage material with a particle size in a smaller range, it is beneficial to further improve the energy density of sodium ion batteries.

[0172] Next, the testing methods of the physical parameters and performance parameters involved in the embodiments of the present application are introduced.

[0173] 1. True density test method

[0174] The true density of the material can be tested by a method known in the art for testing true density. For example, the true density of the material can be tested by using an instrument such as AccuPyc 1340, Austrian Anton Paar DMA 4200M, ZS-102 tap density meter, etc. A specific example of testing true density is given below.

[0175] Sample requirements: Powder (10mL as much as possible); Blocks: Size less than the following requirements: 15mm in diameter, 35mm in height, and a total volume of no less than 6mL. True density refers to the actual mass of a solid substance per unit volume when the material is absolutely dense, that is, the density after removing the internal pores or gaps between particles.

[0176] Place the material to be tested in the true density tester, use helium as the medium, operate the measuring chamber to gradually pressurize to a fixed value, so that the helium expands into the expansion chamber, and the equilibrium pressure of the two processes is automatically recorded by the instrument. According to the law of conservation of mass, the volume of the measuring chamber and the expansion chamber is calibrated by the standard ball, and then the volume of the material is determined to calculate the true density. Apply the Archimedean principle-gas expansion displacement method, and use the Bohr law (PV=nRT) of inert gases with small molecular diameters under certain conditions. Thus, the true volume of the material to be tested is determined by measuring the reduction in the gas capacity of the sample test chamber caused by the sample being placed in the sample test chamber, thereby obtaining its true density, true density=mass / true volume.

[0177] It should be understood that the above fixed value is a value set artificially based on test experience and can be adjusted as needed. After pressurizing to the fixed value, if pressurizing is continued, the volume of helium in the expansion chamber does not change or changes slightly, for example, the volume change rate is less than or equal to 1%.

[0178] 2. Test method for average volume particle size

[0179] Dv50 represents the particle size corresponding to when the cumulative volume distribution percentage of the negative electrode active material reaches 50%. In this application, Dv50 has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer (such as Master Size 300) with reference to GB / T 19077-2016 particle size distribution laser diffraction method.

[0180] 3.BET’s testing method

[0181] The test method refers to the standard GB / T19587-2004 "Determination of specific surface area of ​​solid substances by gas adsorption BET method".

[0182] Take 8g-15g of the sample to be tested and put it into the sample tube, and record the initial mass of the sample to be tested. Load the weighed sample to be tested into the equipment NOVA2000e. Then start degassing, and heat the sample to be tested to 200℃ and keep it for 2h. Then record the mass of the sample to be tested after degassing. Then reload the degassed sample to be tested into the equipment, pour in liquid nitrogen for BET test. Set the nitrogen pressure to 0.08MPa-0.12MPa and the heating temperature to 40℃-350℃. After the test, read the specific surface area from the test results.

[0183] 3. Test method for compacted powder density

[0184] The powder compaction density of the material can be tested by methods known in the art. For example, GB / T 24533-2009 can be used to test using an electronic pressure testing machine (such as UTM7305): a certain amount of powder is placed on a special compaction mold, different pressures are set, the thickness of the powder under different pressures can be read on the equipment, and the compaction density under different pressures can be calculated.

[0185] 4. Test method for sodium ion energy density

[0186] Mass energy density (Wh / kg) = battery capacity (mAh) × voltage platform 3.0V / battery weight.

[0187] 5. Heat spread test method

[0188] The cycled sodium-ion battery is disassembled to obtain the cycled negative electrode sheet, and the negative electrode sheet is ignited to directly observe the heat spread on the negative electrode sheet. More specifically, the prepared battery cell is charged to 4.0V, the battery cell is disassembled in a glove box, the negative electrode sheet is taken out, and cut into 30cm×15cm strips. In an inert glove box, a heat gun (200°C) is used for forced ignition, and the burning rate and burning time are recorded. Thus, the heat spread can also be quantified by the burning rate and burning time. Heat spread rate: v = L / (t_P-t_b)

[0189] Among them, L is the distance between the two temperature sensing lines T-ignition and T-spread, t_P is the time corresponding to the highest temperature at the pole piece spread position, and t_b is the time corresponding to the highest temperature at the ignition position.

[0190] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A negative electrode active material, characterized in that: include: Hard carbon, the true density ρ of the hard carbon satisfies: 1.3 g / cm 3 ≤ρ≤2.0g / cm 3 ; A conversion type sodium storage material, wherein the conversion type sodium storage material can form a compound with sodium.

2. The negative electrode active material according to claim 1, characterized in that The mass content m1 of the hard carbon in the negative electrode active material satisfies: 80%≤m1≤99%; optionally, 85%≤m1≤98%.

3. The negative electrode active material according to claim 1 or 2, characterized in that: The mass content m2 of the conversion-type sodium storage material in the negative electrode active material satisfies: 1%≤m2≤20%; optionally, 2%≤m2≤15%.

4. The negative electrode active material according to any one of claims 1 to 3, characterized in that The conversion type sodium storage material includes at least one of an alloy sodium storage material, a metal oxide sodium storage material, a metal sulfide sodium storage material, a metal selenide sodium storage material, and a metal phosphide sodium storage material.

5. The negative electrode active material according to claim 4, characterized in that The alloy sodium storage material includes at least one of Sn, Ge, Pb, P, Sb, Bi, Si and alloys thereof.

6. The negative electrode active material according to claim 4 or 5, characterized in that: The metal oxide sodium storage material comprises at least one of Sn oxide, Ge oxide, Pb oxide, Sb oxide, Bi oxide and Si oxide; The metal sulfide sodium storage material includes at least one of Sn sulfide, Ge sulfide, Pb sulfide, P sulfide, Sb sulfide, Bi sulfide and Si sulfide; The metal selenide sodium storage material includes at least one of: Sn selenide, Ge selenide, Pb selenide, P selenide, Sb selenide, Bi selenide, and Si selenide; The metal phosphide sodium storage material includes at least one of Sn phosphide, Ge phosphide, Pb phosphide, Sb phosphide, Bi phosphide and Si phosphide.

7. The negative electrode active material according to any one of claims 1 to 6, characterized in that The compound formed by the conversion type sodium storage material and sodium includes at least one of sodium alloy, sodium oxide, sodium sulfide, sodium selenide and sodium phosphide.

8. The negative electrode active material according to any one of claims 1 to 7, characterized in that The average volume particle size Dv50 of the conversion-type sodium storage material satisfies: 5μm≤Dv50≤30μm; optionally, 5μm≤Dv50≤25μm.

9. The negative electrode active material according to any one of claims 1 to 8, characterized in that The gram capacity W1 of the hard carbon satisfies: 150 mAh / g≤W1≤350 mAh / g; optionally, 280≤W1≤350 mAh / g.

10. The negative electrode active material according to any one of claims 1 to 9, characterized in that The discharge gram capacity W2 of the conversion-type sodium storage material satisfies: 300mAh / g≤W2≤2000mAh / g; optionally, 300mAh / g≤W2≤1500mAh / g.

11. A negative electrode plate, characterized in that: The negative electrode sheet comprises the negative electrode active material according to any one of claims 1 to 10.

12. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet as claimed in claim 11.

13. An electrical device, characterized in that: The electrical device comprises the sodium ion battery as claimed in claim 12.

Citation Information

Patent Citations

  • Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof

    CN108475779A

  • Preparation method of porous hard carbon material for sodium-ion battery as well as product and application of porous hard carbon material

    CN114988390A

  • Carbonaceous precursor, carbonaceous anode material, and nonaqueous rechargeable battery

    CN1239592A

  • Hard carbon materials

    US20130252082A1

  • Nonaqueous electrolyte power storage element

    WO2022181516A1